2020
DOI: 10.3390/ph13120418
|View full text |Cite
|
Sign up to set email alerts
|

CDK4/6 and MAPK—Crosstalk as Opportunity for Cancer Treatment

Abstract: Despite the development of targeted therapies and novel inhibitors, cancer remains an undefeated disease. Resistance mechanisms arise quickly and alternative treatment options are urgently required, which may be partially met by drug combinations. Protein kinases as signaling switchboards are frequently deregulated in cancer and signify vulnerable nodes and potential therapeutic targets. We here focus on the cell cycle kinase CDK6 and on the MAPK pathway and on their interplay. We also provide an overview on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 169 publications
(217 reference statements)
2
18
0
Order By: Relevance
“…Additionally, the combination of CDK4 and MAPK pathway inhibitors have shown tumor regression in xenografts models of cancers with KRAS, NRAS or BRAF mutations, particularly BRAF-and NRAS-mutant melanoma, with promising results from phase I clinical studies (29,(48)(49)(50)(51)(52). Clinical trials are currently investigating BRAF and MEK inhibitors in combination with ribociclib in BRAF-mutant melanoma and other solid tumors with BRAFV600 mutations (54). Not only are the two therapies synergistic, but studies have also shown that CDK4 inhibitors may overcome MEK inhibitor resistance (58) and vice versa (59).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the combination of CDK4 and MAPK pathway inhibitors have shown tumor regression in xenografts models of cancers with KRAS, NRAS or BRAF mutations, particularly BRAF-and NRAS-mutant melanoma, with promising results from phase I clinical studies (29,(48)(49)(50)(51)(52). Clinical trials are currently investigating BRAF and MEK inhibitors in combination with ribociclib in BRAF-mutant melanoma and other solid tumors with BRAFV600 mutations (54). Not only are the two therapies synergistic, but studies have also shown that CDK4 inhibitors may overcome MEK inhibitor resistance (58) and vice versa (59).…”
Section: Discussionmentioning
confidence: 99%
“…BRAF-and NRAS-mutant melanoma are particularly receptive to combinatorial therapy [55][56][57][58] and phase I clinical studies have shown promising activity in these tumor types as well 59 . Clinical trials are currently investigating BRAF and MEK inhibitors in combination with ribociclib in BRAF-mutant melanoma and other solid tumors with BRAFV600 mutations 60 . In K-Ras mutant colon cancer, monotherapy with either MEK or CDK4 inhibitors has been disappointing 61,62 ; however synergistic effects were observed in xenograft models of K-Ras mutant colorectal cancer upon treatment with a combination 38,63 , which led to a phase II clinical trial in KRAS-or NRAS-mutant colorectal cancer patients testing binimetinib and palbociclib in combination 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials are currently investigating BRAF and MEK inhibitors in combination with ribociclib in BRAF-mutant melanoma and other solid tumors with BRAFV600 mutations 60 . In K-Ras mutant colon cancer, monotherapy with either MEK or CDK4 inhibitors has been disappointing 61,62 ; however synergistic effects were observed in xenograft models of K-Ras mutant colorectal cancer upon treatment with a combination 38,63 , which led to a phase II clinical trial in KRAS-or NRAS-mutant colorectal cancer patients testing binimetinib and palbociclib in combination 60 . Not only are the two therapies synergistic, but studies have also shown that CDK4 inhibitors are able to overcome MEK inhibitor resistance 64 and vice versa 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Genetic aberrations of members of this pathway are frequent in melanoma, observed in up to 90% of both preclinical and clinical models [ 122 ]. Concerning BRAF-mutant melanoma, an over-activated MAPK pathway is responsible for elevated cellular proliferation by enhancing CDK4/6 functions [ 123 ]. Metastatic BRAF-mutant melanoma patients with high expression of cell cycle genes (cell cycle signature) compared with those with low expression, showed shorter PFS when treated with BRAF inhibitors alone.…”
Section: From the Past To The Future Of Braf-mutant Melanoma Treatmentioning
confidence: 99%